Implikasi Asuhan Keperawatan dari Interaksi Stage Kanker dan Siklus Kemoterapi terhadap Kadar Hemoglobin - Alisarjuni Padang; Linawati Togatorop (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to analyze the effect of cancer stage on hemoglobin levels and to examine the moderating role of chemotherapy cycles in this relationship using Orem’s Self-Care Deficit Theory as a conceptual framework. This analytical cross-sectional study involved 54 cancer patients who had undergone at least one cycle of chemotherapy at H. Adam Malik General Hospital, Medan, Indonesia. Secondary data were obtained from medical records, including cancer stage, number of chemotherapy cycles, and hemoglobin levels. Data were analyzed using a Generalized Linear Model (GLM) with an interaction term to assess moderation effects. The results revealed that cancer stage had a significant negative effect on hemoglobin levels (β = -128.226; p < 0.001), indicating that more advanced cancer stages were associated with lower hemoglobin levels. In contrast, the number of chemotherapy cycles showed no significant effect (β = -0.004; p = 0.609) and did not moderate the relationship between cancer stage and hemoglobin levels (β = 0.025; p = 0.379). These findings suggest that cancer stage is a more dominant factor influencing hemoglobin levels than chemotherapy exposure. From a nursing perspective, the findings highlight the importance of early anemia screening, hematological monitoring, patient education, and self-care support, particularly for patients with advanced-stage cancer. This study was limited by the use of secondary data and a single-center setting, which may restrict the generalizability of the findings. Future studies are recommended to include larger samples, longitudinal designs, and additional clinical variables that may influence hemoglobin levels in cancer patients